Ecce homo : how to become what you are - Nietzsche, Friedrich Wilhelm (Oxford world's classics (Oxford University Press), 2007)
Ecce Homo is an autobiography like no other. Deliberately provocative, Nietzsche subverts the conventions of the genre and pushes his philosophical positions to combative extremes, constructing a genius-hero whose life is a chronicle of incessant self-overcoming. Written in 1888, a few weeks before his descent into madness, the book sub-titled 'How To Become What You Are' passes under review all Nietzsche's previous works so that we, his 'posthumous' readers, can finally understand him aright, on his own terms. He reaches final reckonings with his many enemies - Richard Wagner, German nationalism, 'modern men' in general - and above all Christianity, proclaiming himself the Antichrist. Ecce Homo is the summation of an extraordinary philosophical career, a last great testament to Nietzsche's will. ABOUT THE SERIES: For over 100 years Oxford World's Classics has made available the widest range of literature from around the globe. Each affordable volume reflects Oxford's commitment to scholarship, providing the most accurate text plus a wealth of other valuable features, including expert introductions by leading authorities, helpful notes to clarify the text, up-to-date bibliographies for further study, and much more.